ANALISIS KADAR MERKURI (Hg) DALAM SEDIAAN HAND BODY LOTION WHITENING PAGI MEREK X, MALAM MEREK X, DAN BLEACHING MEREK X YANG TIDAK TERDAFTAR PADA BPOM - Fransisca Wijaya (CALYPTRA, 2014)
X brand morning whitening body lotion, X brand night whitening body lotion, and X brand bleaching unregistered to National Agency of Drugs and Foods Controls (BPOM) are widely used for skin whitening. This research was carried out to analyze mercury (Hg) level which could possibly be found in the preparations. Mercury (Hg) should not be used as skin whitening since it can be accumulated in the body in the long run and eventually can be toxic and damage body organs. Organoleptic test was conducted using miscibility test got from Pharmaceutics The Science of Dosage Form Design to determine emulsion types of each preparation. The results showed that the preparations used had emulsion type of oil in water (o/w). The mercury analysis used the method adopted from 2005’s AOAC (Official Methods of Analysis of AOAC International). The study using ICPS (Inductively Coupled Plasma Spectrometer) showed linearity results with r = 0.9993 and Vxo = 2.02%; wave length used was ƛ = 253.652 nm; LLOD (Lower Limit of Detection) and LLOQ (Lower Limit of Quantitation) values were 0.25 ppm and 0.84 ppm; CV (Coefficient of Variation) for each preparation was 0%; 0.28%; 0.26%; recovery % value for mercury (Hg) in each preparation range from 80.30-101.0%; 80.5-98.5%; 80.25-98.5%. the overall findings implied that this method meets the requirements in terms of linearity, selectivity, precision, LLOD, LLOQ, and accuracy.